Finite element and finite volume simulation and error assessment of polymer melt flow in closed channels - Vaz M.* (2006)
This work aims at evaluating the discretization errors associated to the finite volume and finite element methods of polymer melt flow in closed channels. Two strategies are discussed: (i) Richardson extrapolation and (ii) a posteriori error estimation based on projection/smoothing techniques. The numerical model accounts for the full interaction between the thermal effects caused by viscous heating and the momentum diffusion effects dictated by a shear rate and temperature-dependent constitutive model. The simulations have been performed for the commercial polymer Polyacetal POM-M90-44. Copyright © 2006 John Wiley & Sons, Ltd.